Best Practices for Metabolite Quantification in Drug Development: Updated Recommendation from The European Bioanalysis Forum - Timmerman, Philip; Blech, Stefan; White, Stephen; Green, Martha; Delatour, Claude; McDougall, Stuart; Mannens, Geert; Smeraglia, John; Williams, Stephen; Young, Graeme (Bioanalysis, 2016)
Metabolite quantification and profiling continues to grow in importance in today's drug development. The guidance provided by the 2008 FDA Metabolites in Safety Testing Guidance and the subsequent ICH M3(R2) Guidance (2009) has led to a more streamlined process to assess metabolite exposures in preclinical and clinical studies in industry. In addition, the European Bioanalysis Forum (EBF) identified an opportunity to refine the strategies on metabolite quantification considering the experience to date with their recommendation paper on the subject dating from 2010 and integrating the recent discussions on the tiered approach to bioanalytical method validation with focus on metabolite quantification. The current manuscript summarizes the discussion and recommendations from a recent EBF Focus Workshop into an updated recommendation for metabolite quantification in drug development.